Perinatal emotional skills groups for women and birthing people with borderline personality disorder: outcomes from a feasibility randomised controlled trial - Paul Moran; Debra Bick; Lucy Biddle; Belinda Borries; Rebecca Kandiyali; Farah Mgaieth; Vivan Patel; Janice Rigby; Penny Seume; Vaneeta Sadhnani; Nadine Smith; Michaela Swales; et al. (BJPsych Open)
Background There is no clear evidence about how to support people with borderline personality disorder (BPD) during the perinatal period. Perinatal emotional skills groups (ESGs) may be helpful, but their efficacy has not been tested.